A DESCRIPTIVE ANALYSIS ON THE ROLES AND FUNCTIONS OF THE MUSIC TEAM IN A WORSHIP - Pratowo, Miracle Christian; Kaunang, Meyny; Dumais, Franklin (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The present study is conducted to explore the roles and functions of the worship music team as shown at the curch of GPdI Karmel Tataaran II. This qualitative study uses primary and secondary data. The primary data are obtained through interview from the members of the church and the members of the music team of the church. The primary data are also collected through direct observation. On the other hand, the secondary data comes from the documentation of the previous relevant research and the digital sources from the internet. The obtained data are then analyzed using interactive data analysis which consists of the steps of data reduction, data display, and conclusion or verification. The findings show that the worship music team at the church of GPdI Karmel Tataaran II has a very important role in the worship experiences of the church members. The worship music team help the church members to have praying experiences full of happiness, to have a close relationship with the God, and to create a harmonic and happy atmosphere during the worship. The findings have important implications for the development of church worship and the enhancement of the music team's role in supporting worship objectives. Theoretically and practically, this research contributes to further understanding of the dynamics of music teams in Pentecostal churches.